The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s0102-76382001000400008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo do anel valvar mitral e do ventrículo esquerdo na cardiomiopatia dilatada

Abstract: P M A, Mioto B M, Chabelmann R C, Oliveira S A -Estudo comparativo do anel valvar mitral e do ventrículo esquerdo na cardiomiopatia dilatada. Material e Métodos: Analisaram-se 68 corações humanos adultos, fixados, sendo 48 portadores de CMD de etiologia isquêmica ou idiopática, e 20 corações sem cardiopatia. Obteve-se imagens digitalizadas do perímetro do anel mitral, inserção da cúspide anterior e posterior e da porção fibrosa e muscular. Obteve-se também o perímetro interno do VE, distância do septo ao músc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…From a macroscopic point of view, it was noted that there dilatation in both ventricles of the idDCM group, albeit with distinct morphology, since the expansion of the RVR accompanies the expansion of the equatorial and basal ventricular segments, contrary to what happens in LVR which presents no significant expansion compared to the control group, although there was dilation of equatorial and basal segments at left. In relation to LVR, these findings confirm the results of Juliani [ 22 ] and Hueb et al [ 2 , 3 ] , who claim to not be the degree of left ventricular dilation that determines the degree of dilation of the mitral ring, since they occur independently. This statement has always been a matter of controversy in the literature.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…From a macroscopic point of view, it was noted that there dilatation in both ventricles of the idDCM group, albeit with distinct morphology, since the expansion of the RVR accompanies the expansion of the equatorial and basal ventricular segments, contrary to what happens in LVR which presents no significant expansion compared to the control group, although there was dilation of equatorial and basal segments at left. In relation to LVR, these findings confirm the results of Juliani [ 22 ] and Hueb et al [ 2 , 3 ] , who claim to not be the degree of left ventricular dilation that determines the degree of dilation of the mitral ring, since they occur independently. This statement has always been a matter of controversy in the literature.…”
Section: Discussionsupporting
confidence: 88%
“…Ventricular remodeling characterized by both right and left morphogeometrical changes, provides vicious cycle of functional deterioration, since the heart loses its original anatomical conformation, which is critical to its efficiency. In this context, the valve insufficiency caused primarily by expansion of the atrioventricular rings is of paramount importance [ 1 ] , but despite this relevant fact, the rings expansion mechanism is not completely understood [ 2 - 4 ] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LV dilation almost always stretches the mitral annulus, but contrary to expectations, the degree of dilation of the LV and annulus may worsen somewhat independently from one another [13]. In dilated annulus, the physiological systolic annular contraction is compromised and added to the restriction on systolic excursion of the leaflets, culminates in FMI.…”
Section: Anatomy and Physiology Of The Mitral Valvementioning
confidence: 84%
“…Besides the aforementioned, it is worth noting the morphological study of Hueb et al [13] in 2001, which changed the paradigm that the mitral annular dilatation spared the implantation of the anterior leaflet. The authors demonstrated that this portion of the mitral annulus is also dilated, although to a lesser degree.…”
Section: Brazilian Contribution In the Correction Of The Functional Mmentioning
confidence: 99%